The existence kiai of the islamic boarding school in the community - Abdul Mun'im Amaly; Ahmad Syamsu Rizal; Udin Supriadi (ATTARBIYAH: Journal of Islamic Culture and Education, 2020)
Many consider that Islamic boarding schools are lagging behind the times and are unable to meet the needs of the community. In contrast, Islamic boarding schools are considered as social education institutions, where Kiai plays a central role in uniting boarding school and community. Therefore the purpose of this study is to explore how the part of Kiai in the community. This study uses qualitative approaches and descriptive methods. The data in this study obtained through participant observation, interviews with Kiai, administrators, principals, surrounding communities, and documentation. The results of this study indicate that Kiai can establish strong relationships without stopping with people who are far from religious understanding. Kiai is an influential figure who can integrate all existing social institutions with the institutional boarding school he leads. Further, Kiai is used as a primary role model in thinking, acting, and behave. So that the community recognizes the existence of the Kiai, Kiai can answer every problem that the society faces and accommodate every aspiration of the community.